Water quality control for the Argonauta reactor in Rio de Janeiro - Luciana Carvalheira; Leticia Lins Ramos; Rogerio Chaffin Nunes; Alessandro Mariano Domingues; Francisco Jose de Oliveira Ferreira (Brazilian Journal of Radiation Sciences, 2021)
Different parameters should be monitored at a nuclear facility. Among them, water used in a nuclear reactor must meet strict specifications. The research reactor Argonauta, located in Rio de Janeiro, uses light water as both moderator and coolant. Quality control is the set of measurements to ensure, at any time, products that meet the parameters and standards in force. Then, the quality control of Argonauta’s water encompasses physical-chemical and radiological tests that are performed periodically to monitor deviations in the water parameters specification. These tests include the measurement of pH, conductivity, and gamma spectroscopy. By means of these tests, it is possible to evaluate if the quality parameters of this water meet the requirements defined by the reactor manufacturer and the Radiation Protection standards.  In this way, the safe operation of the Argonauta is guaranteed, besides avoiding unwanted exposures of operators and the environment to the ionizing radiation. This work presents the detailed assays performed in the water quality control. In addition, the obtained results in the last year measurements and highlights of the improvements to be done are also addressed. Moreover, a comparison among other research reactors in Brazil concerning this monitoring is presented. The obtained results indicate that pH, conductivity, and radiological parameters meet the established limits.